Antes de la historia: Anales Máximos, escritura y memoria en la Roma Republicana - Rodríguez Mayorgas, Ana (Gerión. Revista de Historia Antigua, 2008)
This paper addresses the controversial issue of the Annales Maximi’s nature and purpose. The extant textual evidence is examined bearing in mind not only the religious role of the pontifex maximus as a mediator between gods and mortals, but also the status of writing in the early Republic. As opposed to the administrative approach to the Annales, it will be suggested that these records did not have any informative aim, showing instead a ritual use of writing which is at variance with the essence of the Roman historical literature from Fabius Pictor onwards.